Literary, Artistic and Architectural Exchange between Dutch and Polish Avant-Gardes: A Case Study in European Cultural Mobility in the 1920s and 30s - Wenderski, Michał (Dutch Crossing: Journal of Low Countries Studies, 2016)
This paper reflects on cultural mobility in the interwar Europe exemplified by mutual exchange between Dutch and Polish avant-garde formations such as De Stijl or Blok. Polish and Dutch groups and magazines belonged to an international, cross-border network of avant-garde writers, artists and architects who jointly struggled for new, modern art. Within this network, magazines and artists from Poland and the Netherlands were related to each other regardless of apparent cultural and linguistic boundaries – not only via other formations (e.g. French or German), but also directly based on personal contacts between particular representatives of given groups. These relationships enabled direct, mutual and reciprocal exchange of texts and reproductions of artworks and architectural projects between Polish and Dutch magazines. Based on such tangible traces, as well as private correspondence between the artists, I describe the history and the maelstroms of cultural exchange between Dutch and Polish avant-gardes, which – being part of the transnational European avant-garde network – significantly contributed to the development of modern literary, artistic and architectural thought.
Keywords: avant-garde; constructivism; modernism; cultural mobility